Legal Culture, Perspective Reproductions, and the Thai Legal Professionals - Boonchoo Na Pomphet (Faculty of Law Chiang Mai University, 2019)
CMU Journal of Law and Social Sciences (CMUJLSS) is the official peer-reviewed journal of the Faculty of Law, Chiang Mai University. "CMU Journal of Law and Social Sciences" aims to be a publisher of a wide range of high quality academic journals such as original articles, review article in the field of all legal matters, such as public law, private law, criminal law, international law, etc., are related to the knowledge of the social sciences in various fields. Annually, the Journal publishes two issues: the 1st issue during January-June and the 2nd issue during July - December.